The Poem Ennabawia Albadia Between Following And Poetic Creativity A Textual Approach Between Alborda Albowaisiria And Badiiat Mawahib Albadie Fi Ilm Of Albadie Of Ibn Alkhalouf Alqasantini - bouchelaleg, hakima (El Omda in Linguistics and Discourse Analysis, 2022)
This poem, Alborda Albadia, is considered as one of the newly introduced arts about Almadih Ennabawi. It’s rather a part of it. It comes with poetic colours, a mixture of utterance and beautiful sense following the text of Alborda Albowaisiria, which becomes the full roll sample. It recopies from it several texts like the poems of Almowalidiat, Ennaaliat, Alhijaziat and this Borda Albadia. The most important poet followed Albowaisiri is Ibn Alkhalouf Alqasantini through the objective formulation noticed in his poem “Mawahib Albadie Fi Ilm Albadie”